2003
DOI: 10.1046/j.1471-4159.2003.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of prostaglandin F receptor in the spinal cord for tactile pain (allodynia)

Abstract: Prostaglandin F 2a (PGF 2a ) binds to its receptor (FP) to increase the intracellular-free calcium concentration ([Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Here morphine did not inhibit the allodynia induced by ACRO-A and ACRO-B (Figure 4b). In agreement with our recent study demonstrating that functional FP-expressing cells that are involved in PGF 2a -induced allodynia exist in the deeper layer of the dorsal horn (Muratani et al, 2003), the increase in [Ca 2 þ ] i by ACRO-A was more prominent in the deeper layer than in the superficial layer in the dorsal horn (Figure 8a and b). It has been known that micromolar concentrations of ACRO-A are generally required to elicit electrophysiological responses and [Ca 2 þ ] i increase in hippocampal and spinal neurons, in marked contrast to the nM dissociation constant in brain and spinal membranes.…”
Section: T Minami Et Alsupporting
confidence: 93%
“…Here morphine did not inhibit the allodynia induced by ACRO-A and ACRO-B (Figure 4b). In agreement with our recent study demonstrating that functional FP-expressing cells that are involved in PGF 2a -induced allodynia exist in the deeper layer of the dorsal horn (Muratani et al, 2003), the increase in [Ca 2 þ ] i by ACRO-A was more prominent in the deeper layer than in the superficial layer in the dorsal horn (Figure 8a and b). It has been known that micromolar concentrations of ACRO-A are generally required to elicit electrophysiological responses and [Ca 2 þ ] i increase in hippocampal and spinal neurons, in marked contrast to the nM dissociation constant in brain and spinal membranes.…”
Section: T Minami Et Alsupporting
confidence: 93%
“…Indeed, FP receptors mediate ␣B-methylene ATP-evoked allodynia (Kunori et al, 2009). These data are supported by the finding that spinal intrathecal administration of PGF 2␣ produces allodynia by activating FP receptors (Muratani et al, 2003).…”
Section: Fp Receptorsmentioning
confidence: 72%
“…The dorsal horn is a site of a pain transmission, and our result supports other reports on the physiological role of PGF 2 ␣ as a pain modulator ( 1 ). Muratani et al ( 13 ) reported that FPexpressing cells appear in the deeper layer (lamina III and deeper) of the dorsal horn of the spinal cord in conscious mice. Their fi ndings differ slightly from our immunohistochemical data.…”
Section: Discussionmentioning
confidence: 99%